The 'incomplete' failure of political Islam: The Justice and Development Party and the Freedom and Justice Party as case studies. (November 2022) - Magued, Shaimaa
How would Islamists succeed to sustain their rule in spite of their lack of an Islamic blueprint for governance? I draw on an original fieldwork study conducted in Turkey and Egypt from 2010 to 2013 to advance a theory linking Islamists' rule sustainability and political leverage vis-à-vis the state establishment. In contrast with post-Islamism, the results contended that Islamists sustain their rule if they have a high political leverage based on the adoption of a three-fold strategy comprising identification, differentiation, and alliance mobilisation. Based on 45 open-ended and semi-structured interviews conducted with members of Turkey's Justice and Development Party and Egypt's Freedom and Justice Party, findings significantly hold in authoritarian and hybrid regimes in the Middle East.